"No CCP, No New China": Pastoral Power in Official Narratives in China. (13th September 2018) - Zhang, Xiaoling; Brown, Melissa Shani; O'Brien, David
Abstract: Guided by Michel Foucault's concept of "pastoral power, " this article examines the ways in which contemporary discourses within official narratives in China portray the state in a paternal fashion to reinforce its legitimacy. Employing interdisciplinary approaches, this article explores a number of sites in Urumqi, the regional capital of the Xinjiang Uyghur Autonomous Region (XUAR), in order to map how a coherent official narrative of power and authority is created and reinforced across different spaces and texts. It demonstrates how both history and the present day are depicted in urban Xinjiang in order to portray the state in a pastoral role that legitimates its use of force, as well as emphasizing its core role in developing the region out of poverty and into "civilization." 摘要: 本文着眼于探讨在中国新疆这个多事地区, 官方是怎样在不同的公众场景里讲述一个政府关爱百姓的故事。本文作者利用采用并延伸了福柯"牧师关爱"理论, 用多种学科的研究方法 – 对新疆博物馆里的说明文以及展出物品的分析，对新疆日报的分析以及乌鲁木齐市中心友谊路上的路标、广告牌的内容等等的分析，再加上访谈，提出，不论是博物馆里对于历史的讲述， 新疆日报反映当下的叙述， 还是出现在 友谊路上对现在或者将来的话语， 无一不是在讲述同一个故事 – 它不仅代表了官方对历史或者是当下的话语，也展示了国家对子民父爱般的话语，以达到在新疆存在和行为的合法化。